2017
DOI: 10.1016/j.sjbs.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Anti-quorum sensing and anti-biofilm activity of Amomum tsaoko (Amommum tsao-ko Crevost et Lemarie) on foodborne pathogens

Abstract: Cell-to-cell communication or quorum sensing (QS) leads to biofilm formation and causing other virulence factors which are extreme problems for food safety, biofilm related infectious diseases etc. This study evaluated the anti-QS activity of the extract (0.5-4 mg/ml) by using a biosensor strain and biofilm formation by crystal violate assay. Experimental results demonstrated that the overall yield of extract was 11.33 ± 0.3% (w/w). MIC for (Gram positive), Typhimurium (Gram negative) was 1, 2 and 2 mg/ml, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…It has been recently demonstrated that Amomum tsao-ko extract exhibited a high biofilm inhibition when tested against S. typhimurium (51.96%), S. aureus (47.06%), and P. aeruginosa (45.28%) at 4 mg/mL. The same authors demonstrated that this extract can inhibit the violacein production (44.59%) and anti-swarming activity by 4 mg/mL extract on S. typhimurium and S. aureus [ 27 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been recently demonstrated that Amomum tsao-ko extract exhibited a high biofilm inhibition when tested against S. typhimurium (51.96%), S. aureus (47.06%), and P. aeruginosa (45.28%) at 4 mg/mL. The same authors demonstrated that this extract can inhibit the violacein production (44.59%) and anti-swarming activity by 4 mg/mL extract on S. typhimurium and S. aureus [ 27 ].…”
Section: Discussionmentioning
confidence: 97%
“…The presence of different structures of biomolecules in the volatile oils, allows a wider spectrum of bioactivity. Recently, it has been demonstrated that organic extracts from Amommum tsao-ko (Crevost et Lemarie) and Elettaria cardamomum exhibited anti-quorum sensing and antibiofilm activities [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The A. tsaoko ethanol extract exhibited anti-bacterial activity against A. baumannii and P. aeruginosa , whereas the aqueous extract did not. Most previous studies have examined the antibacterial activity of the extract or volatile oil of A. tsaoko , and although some results implied that they had antibacterial effects, this may be due to the larger concentrations used in these studies [ 28 , 29 ]. S. officinalis is a TCM, which be used to treat hemorrhoids, wounds, and ulcers in Eastern Asian countries [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated the anti-QS activity of the A. tsaoko extract using Chromobacterium violaceum a biosensor strain. They showed that it exhibited anti-QS activity in a dose-dependent manner at a concentration range of 0.5–4 mg/mL [ 28 ]. Our study is the first one to use agr reporter strains to evaluate the quorum quenching activity of these extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial quorum sensing is the cell to cell communication by producing the signaling molecules, autoinducers which confer the ability of controlling the gene expression through the detection of small signal molecules (Bai & Rai, 2011;Banerjee et al, 2017;Hentzer & Givskov, 2003;Jakobsen et al, 2012;Singh, Mishra, & Jha, 2017). Moreover, the quorum sensing regulates various bacterial behaviours, such as virulence factor production and motility (Harmsen, Yang, Pamp, & Tolker-Nielsen, 2010;Rahman, Lou, Yu, Wang, & Wang, 2017;Williams, 2007).…”
Section: Introductionmentioning
confidence: 99%